PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PREZI PADA MATAKULIAH ANALISIS VEKTOR - Dian Fitri Argarini; Yunis Sulistyorini (KALAMATIKA Jurnal Pendidikan Matematika, 2018)
Undergraduate students have difficulties in understanding abstract concept of Vector Analysis and need visualization to support learning. Prezi-based instructional media developed by consider visual principle that support Vector Analysis learning. This study aims to describe Prezi-based instructional media development and produce Prezi-based instructional media that is suitable for learning. Development refers to ASSURE development model (Analyze learners, State objectives, Select methods, media and materials, Utilize media and materials, Require learners’ participation, and Evaluate and revise). The research instrument consisted of expert assessment sheets, test questions and student response questionnaires. Instructional media is feasible to be used satisfy aspects of validity and effectiveness. Assessment of the validity aspect based on the experts’ judgment that is on a valid criterion. While the assessment of effectiveness aspects based on test results are on quite good criteria and questionnaire responses of undergraduate students are on excellent criteria. Learning media consists of menu sections and content sections. The menu section consists of an overview of the material that will be presented in the media. The content section consists of material that can be zoomed in and zoomed out according to needs and learning videos to visualize the concept of Vector Analysis.